FAKTOR YANG MEMPENGARUHI KEPATUHAN AWAK MOBIL TANGKI TERHADAP STANDAR OPERASIONAL PROSEDUR PENGISIAN DAN PEMBONGKARAN BBM (STUDI KASUS DI PT. X SEMARANG) - Fatwa Faizah Zaeanina; Bina Kurniawan; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Oil and gas companies have a high risk of danger, namely fires and explosions. Compliance with Standard Operating Procedures has an important role in preventing work accidents. PT. X is a fuel distribution company by operating a tank car for fuel transportation. PT. X has a potential risk such as fire and explosion, especially when filling and dismantling fuel. This purpose of this study is to analyze the compliance of the Tank Car Crew on the Standard Operating Procedure (SOP) for fuel filling and dismantling. This research was a qualitative descriptive study. The subjects of this study were 13 people as the key informants and 5 triangulation informants. The instrument used in this study was indepth interview guides and observation sheets. The results of this study showed  the key  informants had good knowledge and attitudes about compliance with SOP, facilities and infrastructure that supported the realization of compliance with SOP was good enough, namely with the existence of written SOP, training and socialization, friend’s support was good enough to remind each other if there were those who did not do work in accordance with the SOP and the leadership support to do the work in accordance with the SOP is good that is with supervision, warning and reminder to work safely during safety briefings. But the results of observations in the field there were some Tank Car Crew who did not work according to SOP such as did not put down fire extinguisher. The company should increase supervision of the implementation of SOP, especially when filling and dismantling of fuel.